2020
DOI: 10.4322/2526-8910.ctoar1858
|View full text |Cite
|
Sign up to set email alerts
|

A ocupação e a atividade humana em terapia ocupacional: revisão de escopo na literatura nacional

Abstract: Introduction: Human occupations and activities are central themes in occupational therapy studies and interventions in Brazil, although there is no consensus on the use of these terms in the country. Objective: This research aimed to analyze part of the national scientific production of occupational therapy about the use of the terms of occupation and activity. Method: A scoping review of the literature was carried out between 1980 and 2017, using SciELO.br and the Brazilian journals of occupational therapy, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
0
4
0
17
Order By: Relevance
“…Regarding the small number of publications found that contained the term "occupational repertoire" in the text, it is inferred that this would be linked to the very history of Brazilian occupational therapy in the use/disuse of some concepts and constructs. Figueiredo et al (2020) indicate that occupation and human activity are still being debated and are adopted according to the diversity and specificity of the areas and fields in which Brazilian occupational therapy performs its actions (Figueiredo et al, 2020). Salles & Matsukura (2016) e Magalhães (2013) also present subsidies to understand the diverse use of the concepts of occupation and activity throughout the history of occupational therapy in Brazil (Salles & Matsukura, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the small number of publications found that contained the term "occupational repertoire" in the text, it is inferred that this would be linked to the very history of Brazilian occupational therapy in the use/disuse of some concepts and constructs. Figueiredo et al (2020) indicate that occupation and human activity are still being debated and are adopted according to the diversity and specificity of the areas and fields in which Brazilian occupational therapy performs its actions (Figueiredo et al, 2020). Salles & Matsukura (2016) e Magalhães (2013) also present subsidies to understand the diverse use of the concepts of occupation and activity throughout the history of occupational therapy in Brazil (Salles & Matsukura, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the definition of "occupational repertoire" used in the publications is linked to the consideration of human occupation as an object of study and intervention of occupational therapy, based on reference authors in the international context. In this direction, Figueiredo et al (2020), Poellnitz et al (2020) and Salles & Matsukura (2016) found that in the last two decades, "occupation" was more present in publications, which is a result of the national production of knowledge in graduate programs in the area in dialogue with knowledge and discourses produced internationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um movimento de polarização envolveu a profissão, sendo, de um lado, terapeutas ocupacionais que investiam nos modelos ou abordagens internacionais focados na ocupação e, de outro, aqueles que se propunham a pensar a terapia ocupacional a partir de referenciais da filosofia, educação, sociologia e antropologia, adotando o termo atividade, que evoluiu para atividade terapêutica e, posteriormente, atividade humana (Figueiredo et al, 2020;Cruz, 2018;Galheigo et al, 2018).…”
Section: Discussionunclassified
“…É comum observar que o choro é um fator reconhecido como comunicador, que pode levar a suposições de possíveis desconfortos na primeira infância, com alternativas geralmente relacionadas a sono, fome e banho. No entanto, as crianças desde bebê possuem diferentes ocupações que dão significado à vida e que se relacionam a um repertório de atividades no cotidiano 6 . No campo da terapia ocupacional, entende-se atividades como veículos que "possibilitam ao sujeito reconhecer-se e ser reconhecido pelos outros" 7 .…”
Section: Introductionunclassified